Pengaruh Model Discovery Learning Dipadu Lesson Study terhadap Hasil Belajar Mahasiswa Pendidikan Biologi: (The Effect of Discovery Learning Model Combined with Lesson Study on Learning Outcomes of Biology Education Students) - Lely Mardiyanti (BIODIK, 2023)
Combining the learning model with lesson study (LS) can increase the effect of the model in achieving the desired learning outcomes. The purpose of this pre-experimental research is to determine the effect of the discovery learning model combined with LS on the learning outcomes of Biology Education Students. This research was conducted for 1 semester on 30 students who took Plant Physiology Course in the Undergraduated Program of Biology Education, Universitas Negeri Malang using one-group pretest–posttest design. Data on learning outcomes were obtained through essay tests (pretest and posttest) and analyzed using paired t tests. The results of the paired t test inform that there is a big difference in student learning outcomes before (M = 37.5, SD = 13.3) and after learning using the discovery learning model combined with LS (M = 77, SD = 13), t(29) = 18.2, p < 0.001, d = 3.3. Thus, the application of the discovery learning model combined with LS has a major effect on the learning outcomes of Biology Education students in Plant Physiology Course. Key words: Discovery Learning, Lesson Study, and Learning Outcomes Abstrak Memadukan model pembelajaran dengan lesson study (LS) dapat meningkatkan pengaruh model dalam mencapai hasil belajar yang diinginkan. Tujuan dari penelitian pre-eksperimental ini yaitu mengetahui pengaruh model discovery learning dipadu LS terhadap hasil belajar Mahasiswa Pendidikan Biologi. Penelitian ini dilakukan selama 1 semeter pada 30 mahasiswa yang menempuh Mata Kuliah Fisiologi Tumbuhan di Program Studi S-1 Pendidikan Biologi, Universitas Negeri Malang menggunakan one-group pretest–posttest design. Data hasil belajar diperoleh melalui tes esai (pretes dan postes) dan dianalisis menggunakan uji t berpasangan. Hasil uji t berpasangan menginformasikan bahwa terdapat perbedaan besar pada hasil belajar siswa sebelum sebelum (M = 37,5, SD = 13,3) dan setelah pembelajaran menggunakan model discovery learning dipadu LS (M =77, SD = 13), t(29) = 18,2, p < 0,001, d = 3,3. Sehingga, penerapan model discovery learning dipadu LS memiliki pengaruh besar terhadap hasil belajar mahasiswa Pendidikan Biologi pada Mata Kuliah Fisiologi Tumbuhan. Kata kunci: Discovery Learning, Lesson Study, dan Hasil Belajar